Blue-eyed devil [large type] - Parker, Robert B., 1932-2010 (Parker, Robert B., 1932-2010. Cole and Hitch novel., 2010)
When Appaloosa police chief Amos Callico begins shaking down local merchants for protection money, those who don't want to play along seek the help of Cole and Hitch.